Non-Ribosomal Inhibition of The Antibacterial Compound from Ethanol Extract of Gnetii gnemon - Indra Lasmana Tarigan; Afidatul Muadifah; Madyawati Latief (Universitas Negeri Semarang, 2023)
Melinjo (Gnetii gnemonii Folium) is a plant species originating from Peninsular Malaysia and Indonesia, known that contain several bioactive compounds that can be utilized as antibacterial agent. The aims of this study to analyze the profile of the melinjo leaf (Gnetii gnemonii Folium) bioactive compound which has an antimicrobial function by inhibiting the growth of S. aureus and activity in Ribosomal expression. The profile analysis of bioactive compound of melinjo leaf was carried out by screening phytochemical study, HPLC and analysis of antibacterial activity was carried out using turbidimetry method against Bacillus cereus (Bc), Escherichia coli (Ec), and Staphylococcus aureus (Sa). The ethanol extract of melinjo leaves contains tannins, saponins, alkaloids, flavonoids, triterpenoids, with the highest levels being flavonoids 67,117ppm. Analysis of bacterial growth using OD600 showed relatively lower antibacterial activity compared to control. The identification of RNA expression showed that the antibacterial compound of melinjo leaf extract did not have inhibition activity through the ribosome pathway it was thought to have an antibacterial mechanism through non-ribosomal inhibition of bacteria.